(untitled) (R&D Journal, 2018)
The focus of this paper is the experimental and theoretical analysis of the transient behaviour of a two-phase flow natural circulation heat transfer loop using water as the working fluid. The loop is a rectangular vertically orientated 32 mm inside diameter copper pipe of height 7 m and width 8 m. To theoretically simulate the loop, the working fluid is discretized into a series of one dimensional control volumes. When applying the conservation of mass, momentum and energy, and suitable property functions to each control volume, a series of time dependent partial differential equations is generated. Equations are then solved using an explicit finite difference method computer program created in Q-Basic64 programming language. A separated two-phase flow model is applied with frictional multipliers and vapour-liquid void fraction correlations similar to those originally suggested by Martinelli. One vertical side of the loop is heated using electrical heating elements and the other vertical side is cooled using a series of pipe-in-pipe heat exchangers. Transparent pipe lengths are inserted in the loop in order to observe the two-phase flow patterns. The loop is operated in single to two phase operating mode. A reasonable correlation between the experimental and theoretical simulations is found thereby validating the theoretical model. It is concluded that the theoretical model adequately represents the actual transient and heat transfer behaviour of the loop.